(untitled) (The Pakistan Development Review, 1982)
The publication reviewed is number 9 in the series" Applied Statistics and Econometrics" edited by Gerhard Tintner, Pierre Desire Truonet, and Heinrich Strecker. The purpose of the series is to publish papers " too long for ordinary journal articles, but not long enough for books . ... . . Upon acceptance, speedy publication can be promised". The abstracts in English, French, and German, usual in this series, are missing from the copy reviewed. The book consists of ten chapters: sampling theory; multi -stage sampling and other fundamental problems; optimum stratification; variances; sampling with replacement and other theoretical issues; experimental design; information theory; a posteriori raising factors ; order statistics; Bayesian methods. Such an ambitious content within 130 pages requires parsimonious presentation. One chapter has been squeezed into hardly more than four pages. The chapter on a posteriori raising factors will be useful in developing countries and particularly when samples do not work out as designed. It will also be refreshing to those limited to the literature in the English language.